BRISC inactivation alleviates alcohol-induced liver injury in mice - Ting Wang; Wen Zhang; Xian Liu; Kai Liu; Guang-Ming Ren; Shen-Si Xiang; Yi-Qun Zhan; Hui Chen; Hui-Ying Gao; Ke Zhao; Miao Yu; Chang-Yan Li; et al. (Scientific Reports)
Abstract BRCC3 isopeptidase complex (BRISC) is a JAMM subfamily deubiquitinase that has been revealed to be required for optional activation of NLRP3 inflammasome and TLR4/NF-κB signaling pathway. BRISC plays an important role in lipopolysaccharide (LPS)/D-galactosamine-induced acute liver failure, while its functional contribution to alcoholic liver disease (ALD) is still unclear. In this study, we found that the expression of BRISC components was increased in liver tissues of alcoholic hepatitis (AH) animal models and patients with AH. Mice lacking either the scaffold subunit ABRO1 or the catalytic subunit BRCC3 showed attenuated liver steatosis, inflammation, and liver injury compared to control mice after chronic plus binge ethanol feeding. Moreover, pharmacological inhibition of BRISC activity by a BRISC inhibitor thiolutin potently protected mice from ALD development. Preliminary mechanistical studies showed that BRISC deficiency did not directly affect alcohol-induced hepatocyte injury or the translocation of LPS through the damaged gut mucosa after ethanol feeding, but prevented alcohol-induced NLRP3 inflammasome activation in liver. Collectively, our work revealed a previously unknown role of BRISC in ALD and suggested that BRISC may serve as a promising therapeutic target for ALD treatment.